Carthage [videorecording (DVD)] : a journey back in time - Carruthers, Bob; Viner, John (Lost treasures of the ancient world., 1999)
Examine the spectacular wonders of the ancient city which stood on the northern coast of Africa, near modern day Tunis. The earliest artifacts unearthed by archaeologists date from 800 BC.